A new red-emitting material K0.5Na0.5NbO3:Eu3+ for white LEDs. (April 2015) - Sun, Haiqin; Zhang, Qiwei; Wang, Xusheng; Gu, Mu
Graphical abstract: Highlights: KNN: x Eu 3+ red emission material was fabricated via solid-state reaction. KNN: x Eu 3+ shows the intense emission at 615 nm under blue and n-UV excitation. The EuNbO4 second phase significantly enhances the red emission. Abstract: K0.5 Na0.5 NbO3 (KNN): x Eu 3+ materials were fabricated via the conventional solid-state reaction method. The microstructure and photoluminescence property of KNN: x Eu 3+ were investigated. XRD and SEM analyses evidenced that the fergusonite-type structure EuNbO4 were homogeneously precipitated among KNN host. Photoluminescent properties of KNN: x Eu 3+ were significantly influenced by the variations between KNN and EuNbO4 phase. Within the quenching concentrations, the KNN: x Eu 3+ exhibited intense narrow band red emissions centered at 615 nm from 5 D0 → 7 F2 transition with good thermal stability (20–200 °C), under the excitation wavelength at a near-ultraviolet (393 nm) or blue light (464 nm). The red emission intensity reached a maximum at x = 0.20 due to the concentration quenching effect. Nevertheless further increasing the Eu 3+ -doped concentration over x = 0.25 did not decrease the red emission intensity, but significantly enhanced the red emission due to the intrinsic luminescence of EuNbO4 . These results suggest the KNN: x Eu 3+ could be potentially applicable in W-LEDs under near-ultraviolet or blue chip excitation.